2022
DOI: 10.3390/healthcare10020373
|View full text |Cite
|
Sign up to set email alerts
|

How Did the Pandemic Affect Communication in Clinical Settings? A Qualitative Study with Critical and Emergency Care Nurses

Abstract: The objective of the present study was to determine the subjective impact of the pandemic due to COVID-19 on communication, as perceived by nurses working at emergency services and Intensive Care Units at various hospitals in the Region of Murcia (Spain). A qualitative study was conducted based on the content analysis of 12 semi-structured individual interviews. The participant recruitment process was performed through a snowball sampling technique. Four main dimensions, eleven categories, and two sub-categori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 61 publications
2
19
0
2
Order By: Relevance
“…According to previous studies in different healthcare settings (Back et al, 2020 ; Díaz‐Agea et al, 2022 ; Rubinelli et al, 2020 ), our results confirm that, although facemasks contributed to increase the feeling of safety of blood donation staff at the beginning of the pandemic, their impact on professional tasks and relationship with blood donors is relevant. In line with existing data (Rapisarda et al, 2021 ), most healthcare professionals in our study reported discomfort and fatigue related to the continuous use of facemasks, with shortness of breath and headache the most mentioned disturbances.…”
Section: Discussionsupporting
confidence: 88%
“…According to previous studies in different healthcare settings (Back et al, 2020 ; Díaz‐Agea et al, 2022 ; Rubinelli et al, 2020 ), our results confirm that, although facemasks contributed to increase the feeling of safety of blood donation staff at the beginning of the pandemic, their impact on professional tasks and relationship with blood donors is relevant. In line with existing data (Rapisarda et al, 2021 ), most healthcare professionals in our study reported discomfort and fatigue related to the continuous use of facemasks, with shortness of breath and headache the most mentioned disturbances.…”
Section: Discussionsupporting
confidence: 88%
“…Consequently, where the doctor and patient must both wear masks, communication becomes much more difficult [15]. Medical staff associate difficult communication during the Covid-19 pandemic with negative emotions [34]. Quantitative studies emphasize that the quality of patient relationships is important for finding meaning in one's work, leading to reduced risk of burnout [8].…”
Section: Discussionmentioning
confidence: 99%
“…emergency services and intensive care units). 49 Furthermore, nurses have homogenously reported their willingness to resist and develop positive coping and resilient strategies that have been considered protective factors regarding psychological distress during the COVID-19 pandemic. 50 However, compared to the first wave, 17 nurses’ perceptions regarding work in an ever-changing environment have significantly decreased.…”
Section: Discussionmentioning
confidence: 99%